Zredukuj wyrazy podobne i oblicz wartości wyrażeń dla podanych zmiennych.
c)4a+3b-2-6a+b-3 dla a=-2 i b=-1
d)-3a-b+4+4a-b-6 dla a=3 i b=0
e)-3a+3b-4c+2a-3b-c dla a=-3, b=1 i c=2
f)a+4b+2c+3a-6b-c dla a=-2, b=3 i c=10

Proszę o szybkie odpowiedzi ;********

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-17T18:40:48+01:00
C)4a+3b-2-6a+b-3 dla a=-2 i b=-1

-2a +4b -5 = 4 -4 -5 =-5

d)-3a-b+4+4a-b-6 dla a=3 i b=0

a -2b -2 = 3-2 =1

e)-3a+3b-4c+2a-3b-c dla a=-3, b=1 i c=2

-a -5c = 3 -10 = -7

f)a+4b+2c+3a-6b-c dla a=-2, b=3 i c=10

4a -2b +c = -8 -6 +10 = -4
8 4 8
2010-02-17T18:46:01+01:00

c)4a+3b-2-6a+b-3 dla a=-2 i b=-1
-2a+4b-5=4-4-5=-5

d)-3a-b+4+4a-b-6 dla a=3 i b=0
a-2b-2=3-0-2=1
e)-3a+3b-4c+2a-3b-c dla a=-3, b=1 i c=2
-a-5c=3-10=-7
f)a+4b+2c+3a-6b-c dla a=-2, b=3 i c=10
4a-2b+c=-8-6+10=-4
6 3 6